Reproductive biology of Anabas testudineusfrom the Lubuk Siam Lake, Lubuk Siam Village, Siak Hulu Sub District, Kampar District - Mufidah, Muna; Putra, Ridwan Manda; Windarti, Windarti (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractAnabas testudineus is type of fish commonly inhabit the Lubuk Siam Lake in Riau. However, information on reproductive biology of the fish is rare. To understand the biologycal aspects of this fish, astudy was conducted.The fish was sampled once at two weeks for a month period, from July to August 2019. Parameters measured were sex ratio, gonad maturity level, Gonad Somatic Index (GSI), fecundity and egg diameter. Result shown that there was 44 males and 53 females (sex ratio 1:1) . The female’s body is larger and has brighter color than those of the male. The gonadal matury leves in females was 4 in Lubuk Siam River.The Gonad Somatic Index (GSI) of male is around0.40% - 1.13% and female is around 0.57%-4.60%. The average fecundity of the female was 1.986 -3.318. Egg diameter was around 0.53 - 0.58 mm. This result indicated that betok fish were total spawner. Diameter and the evenly indicate the fish is total spawner. The absence of major females in the study area may indicate that the study area is not spawning graund.Keywords: Sex ratio, gonad maturity level, gonad somatix index, fecundity, Total Spawner